Faricimab reverts VEGF-A165-induced impairment of the barrier formed by retinal endothelial cells - Jung, Dominik M.; Fuezy, Isabell; Lytvynchuk, Lyubomyr; Deissler, Heidrun L.; Justus Liebig University Giessen (My University, 2025)
VEGF-A165-induced persistent dysfunction of the barrier formed by immortalized bovine retinal endothelial cells (iBREC) is only transiently reverted by inhibition of VEGF-A-driven signaling. As angiopoietin-2 (Ang-2) enhances the detrimental action of VEGF-A165, we studied if binding of both growth factors by the bi-specific antibody faricimab sustainably reverts barrier impairment. Confluent monolayers of iBREC were exposed to VEGF-A165 for one day before 10–1000 μg/mL faricimab was added for additional five days. To assess barrier function, we performed continuous electric cell–substrate impedance, i.e., cell index, measurements. VEGF-A165 significantly lowered the cell index values which recovered to normal values within hours after the addition of faricimab. Stabilization lasted for two to five days, depending on the antagonist’s concentration. As determined by Western blotting, only ≥100 μg/mL faricimab efficiently normalized altered expression of claudin-1 and claudin-5, but all concentrations prevented further increase in plasmalemma vesicle-associated protein induced by VEGF-A165; these proteins are involved in barrier stability. Secretion of Ang-2 by iBREC was significantly higher after exposure to VEGF-A165, and strongly reduced by faricimab even below basal levels; aflibercept was significantly less efficient. Taken together, faricimab sustainably reverts VEGF-A165-induced barrier impairment and protects against detrimental actions of Ang-2 by lowering its secretion.
Keywords: ddc:610